Effect of Footwear Versus Barefoot on Double-Leg Jump-Landing and Jump Height Measures: A Randomized Cross-Over Study - Kim Hébert-Losier; Caleb Boswell-Smith; Ivana Hanzlíková (International Journal of Sports Physical Therapy)
# Background